1954
DOI: 10.1002/jez.1401270106
|View full text |Cite
|
Sign up to set email alerts
|

The reactions of developing Snapping Turtles, Chelydra serpentina serpentina (Linné), to thiourea

Abstract: Recent reviews on thyroid function by E'leischmann ( '47), Goldsmith ( '49), and Lynn and Wachowski ('51) point up the fact that although the thyroid gland in other classes of vertebrates has been the object of extensive research, relatively little has been done on the gland in reptiles. Moreover, no experimental study on its embryonic function has yet been reported. Nevertheless, the normal developmental pattern of the gland has been worked out for several species, among them the lizards Lacerta agilis (de Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1955
1955
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…In this study, lower incubation temperatures increase incubation time (Table 1; Yntema 1978), and T3 decreases incubation time (Table 3). This result nicely complements an earlier study in which C. serpentina embryos responded to thiourea (a goitrogen or antithyroidal) treatment with slowed developmental rates and increased incubation times (Dimond 1954). Our study also found that T3 treatment decreases hatchling mass (Table 3), which otherwise increases with declining egg temperature down to 24ЊC (Table 1; reviews Figure 2.…”
Section: Effects Of Exogenous Thyroid Hormonessupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, lower incubation temperatures increase incubation time (Table 1; Yntema 1978), and T3 decreases incubation time (Table 3). This result nicely complements an earlier study in which C. serpentina embryos responded to thiourea (a goitrogen or antithyroidal) treatment with slowed developmental rates and increased incubation times (Dimond 1954). Our study also found that T3 treatment decreases hatchling mass (Table 3), which otherwise increases with declining egg temperature down to 24ЊC (Table 1; reviews Figure 2.…”
Section: Effects Of Exogenous Thyroid Hormonessupporting
confidence: 90%
“…The thyroid gland differentiates before this period and responds to antithyroidal agents during this period, suggesting that the gland is functional (Dimond 1954;Ewert 1985). Stages 18-19 are within the sex-determining phase of development (Yntema 1976(Yntema , 1979 and just before the phase that displays positive metabolic compensation (Birchard and Reiber 1995).…”
Section: Thyroid Hormone Application To Eggsmentioning
confidence: 98%
“…Conversely, chicken embryos treated with THs (or TSH) hatch earlier (Balaban and Hill, 1971; Oppenheim, 1973) and premature yolk sac retraction and pipping were noted on E19 after a single injection of T 3 or T 4 on E16 (Decuypere et al, 1991). Similar observations have been made in one non-avian sauropsid species, namely in snapping turtle embryos (Dimond, 1954). …”
Section: Thyroid Hormones and The Hatching Process Of Precocial Birdssupporting
confidence: 82%
“…This study suggests that, at least in the saltwater crocodile, the ontogenic pattern of THs may be similar to that seen in precocial birds. Based on the histology of the thyroid follicles of embryos toward and during hatching, this may also be the case in other reptile species (Dimond, 1954; Miller, 1963). The ontogenic changes seen in deiodinase activities in the embryonic saltwater crocodile also resemble those of the chicken, most notably the marked decrease in hepatic D3 activity that could contribute to increasing plasma T 3 levels toward hatching (Shepherdley et al, 2002b).…”
Section: Thyroid Hormone Levels In the Perihatch Periodmentioning
confidence: 96%
“…Normally, a spike in THs coincides with pipping, an initial break in the eggshell by the embryo. In contrast, exposure to thiourea, a known anti-thyroidal drug, in snapping turtle embryos causes a delay in hatching as well as a decreased growth rate and poor yolk absorption, all of which are known to be thyroid-dependent processes (Dimond, 1954). Thyroid hormonedependent hatching is also evident in reptiles.…”
Section: Hatching and Neonatal Growthmentioning
confidence: 99%